2018
DOI: 10.1002/eco.1981
|View full text |Cite
|
Sign up to set email alerts
|

Water storage dynamics across different types of vegetated patches in rocky highlands of central Argentina

Abstract: Rivers originating in the granitic highlands of seasonally dry central Argentina provide water to 2 million people. These highlands comprise a complex landscape where a matrix of outcropping rock hosts vegetated patches that vary in response to long‐term grazing and fire. We characterized water storage dynamics across 20 sites representing 6 vegetation‐soil conditions with similar mid‐upslope positions in the landscape. We measured temporal and spatial variability of water inputs (rain and fog) and water store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 70 publications
1
9
0
4
Order By: Relevance
“…These observations are in according with Famiglietti, Rudnicki, and Rodell (1998) and Poca, Cingolani, Gurvich, Saur Palmieri, and Bertone (2018), who reported that controlling aspects of SWC dynamic are soil porosity and hydraulic conductivity and topography of the studied hillslope/site. These observations are in according with Famiglietti, Rudnicki, and Rodell (1998) and Poca, Cingolani, Gurvich, Saur Palmieri, and Bertone (2018), who reported that controlling aspects of SWC dynamic are soil porosity and hydraulic conductivity and topography of the studied hillslope/site.…”
Section: Soil Water Content Under Natural Cover: Pre-intervention Psupporting
confidence: 86%
See 3 more Smart Citations
“…These observations are in according with Famiglietti, Rudnicki, and Rodell (1998) and Poca, Cingolani, Gurvich, Saur Palmieri, and Bertone (2018), who reported that controlling aspects of SWC dynamic are soil porosity and hydraulic conductivity and topography of the studied hillslope/site. These observations are in according with Famiglietti, Rudnicki, and Rodell (1998) and Poca, Cingolani, Gurvich, Saur Palmieri, and Bertone (2018), who reported that controlling aspects of SWC dynamic are soil porosity and hydraulic conductivity and topography of the studied hillslope/site.…”
Section: Soil Water Content Under Natural Cover: Pre-intervention Psupporting
confidence: 86%
“…Climate characteristics such as (a) low temperature, (b) high air humidity, (c) high precipitations such as continuous rains-ranging between 47.5 and 149 mm month -1 -drizzles present during the 80% of the rainy days and that represent 30% of the water input (Padrón et al, 2015) and the presence of fog even during less humid periods (Poca et al, 2018), and (d) low evapotranspiration (evapotranspiration = 635 mm year -1 ; evapotranspiration-precipitation ratio = 0.51) due to the extended presence of fog and a dense cloud cover that limit incoming solar radiation (Carrillo-Rojas, Silva, Rollenbeck, Célleri, & Bendix, 2019). Reasons for this are the previously mentioned Andosols properties, the presence of perennial tussock grasses without seasonal changes that have a constant water consumption along the hydrological year and páramo climate characteristics.…”
Section: Soil Water Content Under Natural Cover: Pre-intervention Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Probably, the combined effect of erosion agents with grazing use could be especially stronger in grazing lawns located at higher topographic positions, which are less protected by vegetation cover; there, SOC stocks would be reduced due to the reduction of soil profile depth. In that case, greater efforts should be directed to protect vulnerable upland soils, which have been described as invaluable buffers of peak stormflows and sediment yields in these headwater catchments (Poca et al 2018b).…”
Section: Discussionmentioning
confidence: 99%